Technology of manufacturing the reliable silicon photoconverters with long operation time - Guseynov, N.A.; Askerov, Sh.Q.; Aslanov, Sh.S.; Agaev, M.N.; Gasanov, M.H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
We offer to use an amorphous metal alloy Al₈₀Ni₂₀ as ohmic contact and current-collecting tracks to silicon photoconverters (PC) based on p-n junctions. Technological processes for production of silicon photosensitive structures and film coatings with an amorphous structure are described. The data of the X-ray structure analysis of the metal alloy Al₈₀Ni₂₀ confirming amorphism were obtained. The key PC parameters are determined.